The probable modal split of commuters in Jalan Pudu with the introduction of LRT System 1 / Esrifairuz Subohi - Subohi, Esrifairuz (1996)
The Light Rail Transit (LRT) System 1 project for Kuala Lumpur is going to be completed by the year 1996, followed by a number of other privatization of public transport system project such as Monorail, City Buses and traffic management scheme to shift the current Modal Split of 70:30 (Private Transport : Public Transport) towards Public Transport and alleviate the city from traffic congestion by the year 2020. The overall choice between private and public transport is complex and more often reflects policy issues rather than the relative attributes of the journeys by each mode. This study will discuss the probable modal split of commuters in Jalan Pudu with the introduction of the LRT system 1. In this research a few objectives have been identified: i. to determine the existing characteristic of the journey to be made by the private car users, ii. to determine the existing modal split between the usage of private vehicle against public transport, iii. to determine the characteristics of the person making the journey, iv. to know whether they are willing to leave their car and travel by using the LRT v. to give recommendation on how to attract the commuters to shift to use the LRT. By having all the above objectives, it is hopes that this research can somehow be the reference and guidance to those who are interested in continuing this topic.